Clinical risk score to recognize macrosomia at the time of delivery - Patumanond J. (2014)
Objective: To develop a clinical risk score to help in recognizing macrosomia at the time of delivery. Methods: A case-control data analysis was conducted at a university-affiliated general hospital in Lamphun, Thailand. Macrosomic cases were 67 women who delivered babies weighing at least 4,000 g. Controls were 779 women with babies weighing between 2,500 g. and < 4,000 g. The best predictors were selected by multivariable logistic regression and transformed into clinical risk scores. Result: The best combination of predictors included parity, gestational age at delivery, weight at delivery and symphysis-fundal height. The scores predicted macrosomia correctly with an AuROC of 94.1% (95% CI; 92.3, 95.6). The likelihood ratio of positive for macrosomia was 0 in the low risk category and 10.68 (95% CI; 7.76, 14.68) in the high risk. Conclusion: A simple clinical risk score may help obstetricians suspect macrosomia at the time of delivery in areas where antenatal care services are inadequate.